2016
DOI: 10.1177/0021998316631812
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of mechanical and dynamic mechanical properties of multiwalled carbon nanotube-based ethylene–propylene copolymer composites mixed by masterbatch dilution

Abstract: A two-step masterbatch mixing technique was studied for preparation of carbon nanotube-filled ethylene–propylene diene elastomer compounds, and compared to conventional one-step mixing process. In the two-step process, a masterbatch compound with carbon nanotube content of 50 parts per hundred was prepared by melt-mixing ethylene–propylene diene elastomer. This material was then compounded with pristine ethylene–propylene diene elastomer and composites with different carbon nanotube concentrations were compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…The replacement of small amounts of CB by NDs can be expected to shorten the vul-canization time due to the high thermal conductivity of NDs [37,38] and thus due to the more efficient thermal energy transfer and faster temperature increase in rubber. This kind of behavior has been observed for CNTs [39] and for the CNT-CB filler combinations [14] as well as in the earlier ND studies [40]. However, the effect of NDs was opposite in the current case.…”
Section: Resultssupporting
confidence: 85%
“…The replacement of small amounts of CB by NDs can be expected to shorten the vul-canization time due to the high thermal conductivity of NDs [37,38] and thus due to the more efficient thermal energy transfer and faster temperature increase in rubber. This kind of behavior has been observed for CNTs [39] and for the CNT-CB filler combinations [14] as well as in the earlier ND studies [40]. However, the effect of NDs was opposite in the current case.…”
Section: Resultssupporting
confidence: 85%
“…The similar effect of CNTs was found in earlier studies. 22 This is due to the increased thermal conductivity of the PCM-NR composite. Surprisingly, NDs increase the curing time although they also improve the thermal conductivity of the composite as seen in Figure 2.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that good CNT dispersion in NR compound can be achieved by solid mixing up to 5 phr filler concentration. 21,22 However, higher filler concentrations are often required for high thermal conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of studies that have followed this approach have reported excellent mechanical properties at even high filler loadings. [107][108][109][110][111][112] The group of Potschke has investigated extensively the effect of CNTs in a number of polymeric matrices via melt mixing and masterbatch dilution. In their research, they evaluated a number of important characteristics for the efficient dispersion of CNTs within a polymer matrix such as the screw profile, the temperature profile, the rotation speed, the injection moulding parameters and the specific mechanical energy.…”
Section: Carbon Nanotube Nanocompositesmentioning
confidence: 99%